Taxpayer Knowledge, Service Quality, Tax Sanctions, and Awareness in Enhancing Property Tax Compliance in Jember Regency - Soetjahyo, Soetjahyo; Cahyono, Dwi; Sanosra, Abadi (SENTRALISASI, 2025)
Taxation plays a pivotal role in economic development, serving as a primary revenue source and a tool for achieving broader social objectives. This study examines the impact of taxpayer knowledge, service quality, and tax sanctions on tax compliance, with taxpayer awareness as a mediating variable, using the Integrated Tax Compliance Model. Data were collected from 400 PBB taxpayers in Jember Regency through a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that taxpayer knowledge, service quality, and tax sanctions significantly influence both taxpayer awareness and compliance. Additionally, taxpayer awareness mediates the relationships between these independent variables and compliance, highlighting its pivotal role. The study offers theoretical and practical contributions by demonstrating the integrated effects of these variables, providing a comprehensive understanding of taxpayer behavior, and guiding policymakers in formulating more effective tax strategies. This research underscores the importance of educational programs, service improvements, and balanced sanctions to enhance voluntary compliance, supporting sustainable regional development.